2001
DOI: 10.1037/0022-006x.69.3.516
|View full text |Cite
|
Sign up to set email alerts
|

Does smoking abstinence self-efficacy vary across situations? Identifying context-specificity within the Relapse Situation Efficacy Questionnaire.

Abstract: According to self-efficacy and relapse theories. abstinence self-efficacy (ASE) ratings should be context-specific: they should vary across situations. This variability may be important, as it could signal high-risk for relapse situations. In this study, confirmatory factor analysis was used to identify situational variability in a novel ASE assessment (Relapse Situation Efficacy Questionnaire. or RSEQ). Results supported a hierarchical structure, where both context-specific and unidimensional measures of ASE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
96
2
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 38 publications
(91 reference statements)
8
96
2
7
Order By: Relevance
“…Social or food situations in which people smoke were also identified in previous studies. 2,33 However, what is new in this study is that we have identified both contexts or situations and specific cues that can produce smoking craving. This knowledge is necessary when developing VEs that aim to reproduce real situations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Social or food situations in which people smoke were also identified in previous studies. 2,33 However, what is new in this study is that we have identified both contexts or situations and specific cues that can produce smoking craving. This knowledge is necessary when developing VEs that aim to reproduce real situations.…”
mentioning
confidence: 99%
“…28,30 Shiffman et al (1996) used electronic diaries in order to avoid retrospective methodology in the recording of craving or relapse situations, finding that most lapses (78%) were associated with smoking cues and eating or drinking situations. Another study, which assessed the psychometric properties of 12 photos related to smoking, yielded excellent results, 31 while several studies assessing smokers' self-efficacy in diverse situations [32][33][34] offer a starting point for the use of reliability stimuli in VE-CET. In order to generalize the use of VR to clinical contexts, it is necessary to develop more diverse VEs based on larger samples of smokers' reports and on previous literature, with the aim of exposing participants to a greater number of situations and enhancing the probability of generalization of extinction.…”
mentioning
confidence: 99%
“…The level of selfefficacy represents the degree to which an individual believes he/she can successfully change a particular behavior. Self-efficacy has been shown to successfully predict change in a variety of behaviors and is superior to past performance as a predictor of future behavior Wamsteker et al, 2005;Staring & Breteler, 2004;Gwaltney et al, 2001;Velicer et al, 1990;Dennis & Goldberg, 1996;Bandura, 1986;Condiotte & Lichtenstein, 1981).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Self-efficacy has been among the most analyzed psychosocial constructs in both nutrition (Anderson et al, 2007;Linde et al 2006;Cullen et al 2001;Fontaine & Cheskin, 1997) and smoking cessation studies (Staring & Breteler 2004;Gwaltney et al, 2001;Scholte & Breteler, 1997;Gulliver et al, 1995;Haaga et al 1993). The level of selfefficacy represents the degree to which an individual believes he/she can successfully change a particular behavior.…”
Section: Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation